A eletrooxidação de etileno glicol: estudo dos caminhos reacionais em superfícies de PtRu em meio alcalino - Nascimento, Diego Rogério Pinto do (2016)
Short chain alcohols have been studied for possible use in fuel cells. The ethylene glycol oxidation electrode Pt and PtRu, in alkaline medium, showed great efficiency and increasing the current density was evidenced by a gradual rise in temperature, which confirms that the temperature is a significant factor for the electrooxidation glycol favoring the formation of oxygenated species and facilitating the oxidation adsorbates. The ethylene glycol oxidation products on the surfaces of Pt and PtRu were identified by high-performance liquid chromatography and the presence of glycolaldehyde was confirmed as alcohol oxidation product of Pt and glycolaldehyde and glicoato on surfaces of PtRu. Bimetallic PtRu electrodes were prepared by electrodeposition in five different proportions: 94:06; 90:10; 88:12; 83:17 and 77:23. The percentage of both metals was determined by EDX technique. significant currents were obtained from these electrodes, since they were used as working electrodes. The best results are related to glycol oxidation on PtRu electrode (77:23), because it made possible the oxidation of alcohol to study less anodic potential, which was verified by glycol oxidation beginning around 0.25 V, as well have caused a significant decrease in the region characteristic of hydrogen. Thus, the PtRu alloy catalyst is considered to be good catalyst for CO oxidation and ethylene glycol in the alkaline medium. The number of moles to glycol oxidation products were determined at temperatures of 25 to 55 ° C for both a flat eterodo Pt as to eletrodeposito PtRu (77:23) and its activation energy was determined for each electrode the current data from the apalicação equaçãi Arrhenius, meeting 24.29 and 32.02 kJ.mol-1 to the flat electrode of Pt and PtRu eletrodepositdos respectively.